Optimalisasi Produktivitas UKM di Probolinggo Melalui Inovasi Teknologi Informasi - Kamil Malik (Jurnal Masyarakat Mengabdi Nusantara, 2023)
This study investigates the impact of information technology education and mentoring on enhancing the productivity of Small and Medium Enterprises (SMEs) in Probolinggo Regency. Involving 30 SME participants, the study utilized qualitative methodologies, including interviews, surveys, and observations, to assess changes in participants' knowledge, attitudes, and practices towards information technology. The results indicate a significant increase in understanding and use of digital technology post-activity, with 85% of participants reporting improved knowledge and 90% exhibiting a positive attitude towards the use of technology in their businesses. Practical implementation of new skills was observed in 65% of participants, who successfully activated and managed accounts on online marketplaces within two weeks after training. The study concludes that effective education and mentoring in information technology are crucial catalysts for digital adaptation in SMEs, especially in rural areas, and highlights the need for more tailored training approaches for older participants.